Sea-Level Indicators - Evelpidou, N.; Pirazzoli, P. (Environmental Management and Governance: Advances in Coastal and Marine Resources, 2015)
Because changes in sea level may have a great impact on the distribution of mineral resources, the exploration and exploiting of these resources should not ignore the changes in sea level that may have occurred in the past in the area considered. The study of relative sea-level changes is an essential element of ocean observation and technological advances are often necessary to improve this study that includes the determination of levels (elevation or depth), chronological estimations, and the identification of appropriate sea-level indicators. Indicators of fossil or present-day sea-level positions are the most important elements for a sea-level reconstruction, because they provide information not only on the former level but also on the accuracy of the reconstruction. A classification is proposed of the main criteria that can be used to deduce appropriate sea-level indicators from geomorphological, stratigraphical, biological or archeological coastal data. Two cases studies are used as examples of sea-level reconstructions that may be useful to clarify the geology in certain areas, or to coastal engineering and coastal protection: (1) on the impact of the recent sea-level rise in the interpretation of sea-level indicators; and (2) on the foreseeable impacts of the predicted near-future sea-level rise on the coasts of NE Italy.